Habilidades comunicativas em pacientes com Migrânea - Caroline Martins de Araújo (2012)
Objective: Migraine is a very common disease, achieving 15% of the population. Many studies attest to cognitive changes in migraine and, starting from this context, it was aimed to identify if the patients with migraine followed at the Neurology Service Migraine Ambulatory at Hospital das Clínicas – UFMG showed any changes in their communicative abilities. Methods: A cross-sectional study was made using a structured interview in 30 patients with migraine and 30 controls. To characterize the sample a sample characterization Form was produced. To evaluate impact and life quality in patients with migraine the following instruments were used: HIT-6, MIDAS and SF-36. The MAC, Phonological Awareness Test, Syntax Awareness Test, MSV, MSNV, LS, TPTD e TPTF were used to evaluate communicative abilities. Results: Most patients showed a very high impact grade of migraine (46,7%) and serious incapacity (56,7%). The SF-36 showed the worst score into the group with migraine than in control. Patients witn migraine showed the worst scores at MAC when compared to controls. At the Phonological Awareness Test it was observed significative statistically differences within all items except for the syllabic synthesis. Statistically different differences were also observed at MSNV, LS, TPTD and TPTF. Association between impact grade or incapacity grade motivated by migraine and communicative abilities was not observed. Conclusion: Patients with migraine showed communicative changes when compared to controls. Such changes are not associated to migraine seriousness.